Comparison of Lactobacillus strains with respect to bile salt hydrolase activity, colonization of the gastrointestinal tract, and growth rate of the murine host. - Bateup, J M (1995)
The significance of bile salt hydrolase production by lactobacilli in the microecology of the murine intestinal tract has not been extensively studied previously. Assays of bile salt hydrolase (sodium taurocholate as substrate) associated with cell extracts of five Lactobacillus strains of murine origin gave a range of activities (from 915 nmol of cholate released per mg of protein per 30 min to none detected). All of the strains tested colonized the murine gastrointestinal tract equally well. The growth rates of mice were not affected by colonization of their intestinal tracts by lactobacilli whether or not the bacteria produced bile salt hydrolase.